Pengaruh Latihan Tendangan Menggunakan Kaki Dalam dan Punggung Kaki Penuh terhadap Ketepatan Shooting ke Gawang pada Pemain PS UNIMUDA Sorong - Musa Kambu; Waskito Suryo Aji Putro; Leo Pratama (Jurnal Muara Olahraga, 2025)
This study aims to determine the effect of shooting practice using the inside of the foot and full instep on shooting accuracy at the goal of PS Unimuda Sorong players. This study uses an experimental method with a "two group pre-test post-test design" design. The population in this study were PS Unimuda Sorong players totaling 22 students. The results of the analysis show that: (1) There is an effect of shooting practice using the inside of the foot on shooting accuracy of PS Unimuda Sorong players with a calculated t of 7.178> t table 2.20, and a significance value of 0.000 <0.05, with a percentage increase of 39.29%.